The voyages of Doctor Dolittle - Lofting, Hugh, 1886-1947.; Hague, Michael (New York : HarperCollins, 2001)
When his colleague Long Arrow disappears, Dr. Dolittle sets off with his assistant, Tommy Stubbins, his dog, Jip, and Polynesia the parrot on an adventurous voyage over tropical seas to floating Spidermonkey Island.
Originally published in 1922.
5.9
5-8
Keywords: Animals -- Fiction; Fantasy; Voyages and travels -- Fiction; Animals -- Fiction; Voyages and travels -- Fiction; Fantastic fiction